An improved algorithm of white matter hyperintensity detection in elderly adults - T Ding; AD Cohen; EE O’Connor; HT Karim; A Crainiceanu; J Muschelli; O Lopez; WE Klunk; HJ Aizenstein; R Krafty; CM Crainiceanu; DL Tudorascu (NeuroImage: Clinical, 2020)
Automated segmentation of the aging brain raises significant challenges because of the prevalence, extent, and heterogeneity of white matter hyperintensities. White matter hyperintensities can be frequently identified in magnetic resonance imaging (MRI) scans of older individuals and among those who have Alzheimer’s disease. We propose OASIS-AD, a method for automatic segmentation of white matter hyperintensities in older adults using structural brain MRIs. OASIS-AD is an approach evolved from OASIS, which was developed for automatic lesion segmentation in multiple sclerosis. OASIS-AD is a major refinement of OASIS that takes into account the specific challenges raised by white matter hyperintensities in Alzheimer’s disease. In particular, OASIS-AD combines three processing steps: 1) using an eroding procedure on the skull stripped mask; 2) adding a nearest neighbor feature construction approach; and 3) applying a Gaussian filter to refine segmentation results, creating a novel process for WMH detection in aging population. We show that OASIS-AD performs better than existing automatic white matter hyperintensity segmentation approaches. Keywords: Brain, WMH segmentation, Alzheimer's disease, OASIS, MRI, Statistical methods neuroimaging